2015
DOI: 10.1111/tri.12682
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for donation after circulatory death kidney transplantation in Europe

Abstract: SUMMARY Donation after circulatory death (DCD) donors provides an invaluable source for kidneys for transplantation. Over the last decade, we have observed a substantial increase in the number of DCD kidneys, particularly within Europe. We provide an overview of risk factors associated with DCD kidney function and survival and formulate recommendations from the sixth international conference on organ donation in Paris, for bestpractice guidelines. A systematic review of the literature was performed using Ovid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 106 publications
1
24
0
2
Order By: Relevance
“…For example, the use of large doses of vasoactive drugs before donation and persistent hypotension in the donors before cardiac death may cause kidney injury. Therefore, it is critical to assess and improve the quality of DCD kidneys prior to transplantation .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of large doses of vasoactive drugs before donation and persistent hypotension in the donors before cardiac death may cause kidney injury. Therefore, it is critical to assess and improve the quality of DCD kidneys prior to transplantation .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significant potential for organ DCD by small children, recovery and transplantation of small pediatric DCD donor kidneys remain uncommon . As recently as in 2015, a systematic review by a multinational European expert group concluded with the clinical consensus recommendation that “DCD kidneys from young children should be used with caution.” It is therefore not surprising that only isolated case reports and very few small case series on transplantation of kidneys from very small pediatric DCD donors have been published to date. Small pediatric DCD kidney transplantation remains so uncommon that even larger recent national registry reviews of recovery, utilization, and transplantation of kidneys from small pediatric donors neither specify the proportion of DCD donors nor stratify their outcomes analyses by DCD vs DBD donor status (because of the very low absolute number of DCD cases) …”
Section: Discussionmentioning
confidence: 99%
“… Regional normothermic reperfusion: There is emerging experimental and clinical evidence that warm ischaemic injury to vulnerable transplantable organs can be improved if the transplantable abdominal organs are re‐circulated with oxygenated blood prior to explantation by restoring cellular substrates and reducing levels of degradation products . It is vital that protocols supporting such interventions describe how reperfusion will be reliably restricted to the relevant organ bed(s), thereby avoiding inadvertent restoration of cerebral blood flow.…”
Section: Post‐mortem Interventions and Organ Retrievalmentioning
confidence: 99%